Emergency Department Management of a Multiple Trauma Patient With a Left Ventricular Assist Device - Jessica Rando; Alexander Bedard; Raymond Ten Eyck (Association of American Medical Colleges, 2014)
Abstract Introduction Patients with a left ventricular assist device (LVAD) can be difficult to assess as most do not have a measurable blood pressure, pulse, or oxygen saturation. Instead, assessment relies on mental status and Doppler. Often these patients are on anticoagulation and can have significant bleeding during trauma. Methods During this simulation case, a 79-year-old male is brought in to the Emergency Department via Emergency Medical Services after being involved in a motor vehicle collision. The patient is noted to have an LVAD in place. The physician will need to manage the patient as a typical trauma, while considering any complications that can develop secondary to having an LVAD. Results Three residents separately participated in this simulation case. All three participants effectively managed the trauma aspect of this simulation while managing all complications provided by an LVAD. They stated that it was an effective learning case and all three met all educational objectives. Discussion This simulation case can be effectively used to train residents and physicians on the special considerations associated with an LVAD during a trauma. Participants suggested this case be used for residency level two or higher.